Políticas públicas LGBTQIA+ e as dinâmicas de desagendamento governamental no Brasil - De Vitto, Victor Augusto Nunes (Universidade Federal de São Carlos, 2023)
In the 1980s, brazilian redemocratization coexisted with an unprecedented political organization of non-heterosexual-cisgender people in the sense of pressuring governments for the recognition of their civil and social rights. Although, at first, the political action of these subjects was arranged through a thematic network strongly linked to the Public Health subsystem in the search to reduce the harm of the then emerging AIDS epidemic, the agenda of these social movements never was limited only to the promotion of sexual health and HIV prophylaxis. In 1995 inaugurated a moment of incremental inclusion of the demands of these groups in the governmental agenda-setting, with emphasis on civil union and the punishment of discriminatory acts, inaugurating a relative action of the Executive and the Judiciary with the common objective of affirming specific rights that It was opposed to the legislative omission regarding these historic claims, after all the LGBTQIA+ movements are still unable to obtain the approval of a specific legal framework in their favor in Congress. In line with the moderate affirmation of an incomplete and judicialized citizenship, from 2011 onwards these initiatives were the object of opposition responsible for the sudden rescheduling of actions previously built. Public Policy Theory borrowing the Punctuated Equilibrium Model to understand that this process social change of attention and, consequently, of the governmental agenda towards the lack of responsibility for leveraging an integral LGBTQIA+ citizenship was supported by public policy images of moralizing content, loaded with symbols and emotional appeals contrary to these groups, strategies and courses of political action that, in addition to emptying a previous affirmative governmental action, blocked discussions and respective deliberations of new demands from these social movements. In order to understand the expansion of political conflict arising from this “anti-gender offensive”, a multimethod research design was adopted based on constructivist Grounded Theory and Textually Oriented Discourse Analysis in the construction of research surveys implemented in sixteen individual interviewssemi-structured interviews with activists and allies with a history of participation and leadership in the construction of LGBTQIA+ public policies. Thematic and focused qualitative coding was performed using the MAXQDA Pro Analytics 12.3 application, followed by subsequent discourse analysis that mapped modalization and politeness traits in the discourse of activists and allies about four anti-LGBTQIA+ images: “gay booklet", “gay cure”, “gender ideology” and “gay blood”. As a result, the high degree of negative politeness and objective epistemic modalization mobilized in the discourse of these interviewed subjects regarding the definition of a "policy dynamics of unscheduling" stands out, given the eminently metaphorical and unscientific dimension of such Christian interreligious interpretations on the pertinence of LGBTQIA+ rights as government priorities.
LGBTQIA+ policies and the dynamics of unscheduling brazilian governmental agenda
Keywords: Agenda governamental; Government agenda; Imagens de política pública; Policy images; LGBTQIA+; Polidez; Politeness; Modalização; Modalization; Teoria fundamentada em dados; Grounded theory; CIENCIAS HUMANAS::CIENCIA POLITICA::POLITICAS PUBLICAS